Production of carboxylates from high rate activated sludge through fermentation. (October 2016) - Cagnetta, C.; Coma, M.; Vlaeminck, S.E.; Rabaey, K.
Highlights: pH of 7 and 35 °C were found as optimal parameters for A-sludge fermentation. Fermentative inoculum presence enhances carboxylate production from A-sludge. A-stage sludge produces more VFA compared to waste activated sludge values. Iron content is directly proportional to CH4 but not to carboxylate production. Abstract: The aim of this work was to study the key parameters affecting fermentation of high rate activated A-sludge to carboxylates, including pH, temperature, inoculum, sludge composition and iron content. The maximum volatile fatty acids production was 141 mg C g −1 VSSfed, at pH 7. Subsequently the potential for carboxylate and methane production for A-sludge from four different plants at pH 7 and 35 °C were compared. Initial BOD of the sludge appeared to be key determining carboxylate yield from A-sludge. Whereas methanogenesis could be correlated linearly to the quantity of ferric used for coagulation, fermentation did not show a dependency on iron presence. This difference may enable a strategy whereby A-stage sludge is separated to achieve fermentation, and iron dosing for phosphate removal is only implemented at the B-stage.